Pre-diabetes and Type 2 Diabetes Status in Overweight and Obese Children in a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Child Health, 2021)
Introduction: Obesity in childhood is associated with many co-morbid conditions; one of them is alteration of glucose metabolism.Materials and Methods:This cross-sectional study was conducted among 100 overweight and obese children aged 5-16 years to determine the status of pre-diabetes (IFG and IGT) and type 2 diabetes mellitus (T2DM), attending the OPD, BSMMU, Dhaka. All overweight/obese children were included according to BMI for age and sex using CDC growth chart. Children taking steroid for any cause or having any endocrine disorder or syndrome was excluded from the study. Anthropometry and blood pressure measurement were done and skin manifestations of insulin resistance were looked for. Fasting lipid profile and oral glucose tolerance test (OGTT) was done for each child.Result: Among the studied children 62% were male and 38% female, 77% were obese and 23% were over weight. Evidence of insulin resistance were found among most of the children and most common evidence was dyslipidemia (80%) followed by acanthosis nigricans(76%). Skin manifestation of polycystic ovary syndrome (PCOS) was found in 3% of children. Impaired fasting glucose (IFG) was found in 4% and Impaired Glucose Tolerance (IGT) was found in 7% of children among them 4% had both IGT and IFT. No child was found diabetic in this study.Conclusion:Altered glucose metabolism was present in overweight and obese children of our children, so screening is recommended.Bangladesh J Child Health 2020; VOL 44 (3) :143-147